Coordination of directional overcurrent and distance relays based on nonlinear multivariable optimization - Tahseen Ali Abd Almuhsen; Ahmed Jasim Sultan (Institute of Advanced Engineering and Science, 2020)
To ensure stability, security, and protection of electrical equipment from the damage the suitable coordination must be made in interconnected networks. In this paper, the nonlinear multivariable optimization techniques have been used with different performance indexes: Sequential quadratic programming (SQP), Sequential quadratic programming legacy (SQP-Legacy), Interior-Point and Active-Set for IEEE- 8 bus test system. This system consists of twenty-eight protective relays divided into fourteen directional overcurrent relays (DOCR) and fourteen distance relays (DR). It has been tested in the ETAP environment to obtain three-phase short circuit current at the near and far end faults and operating time for all DOC relays for near-end fault as well as test the second zone time for distance relays (TZ2) with pilot signal (WP)and without pilot signal (WOP) of the proposed algorithm was used to reduce overall operating time of DOC relays and obtain optimal values for time multiplier setting (TMS) and TZ2 with the different coordination time interval (CTI) between main and backup relays. The simulation results were validated in ETAP program prove that the effectiveness of the Active-Set to minimize the TMS and TZ2 for the system.